(untitled) (International Journal of Engineering and Computer Science, 2017)
The growing computing abilities of wise phones, these idle phones constitute a significant computing infrastructure. Therefore, to have an enterprise which gives its employees with wise phones, we reason that a computing infrastructure that leverages idle wise phones being billed overnight is definitely an energyefficient and price-effective option to running certain tasks on traditional servers. Every evening, many wise phones are blocked right into a source of energy for recharging battery. While parallel execution models and schedulers exists for servers, wise phones face a distinctive group of technical challenges because of the heterogeneity in CPU clock speed, variability in network bandwidth, minimizing availability than servers. Within this paper, we address a number of these challenges to build up CWC-a distributed computing infrastructure using wise phones. We next investigate whether continuous usage of the CPU affects the CPU efficiency. Our evaluations utilizing a test bed of 18 Android phones reveal that CWC’s scheduler yields a make span that’s 1.6x quicker than other simpler approaches. We implement and evaluate a prototype of CWC that utilizes a manuscript scheduling formula to reduce the make length of some computing tasks.